Non-ferrous metal industry : Industrialization of developing countries: Problems and prospects - United Nation; United nations (New York : United Nations Publication, 1969)
This studies explains wide range of problems relating to industrialization presented to the symposium-by the UNIDO secretariat and by participating Government, international organizations and observers.
Includes bibliographies.
asm: 21/01/19
Loans
Keywords: Nonferrous metals